Metacommunity organization in an intermittent riverin Brazil: the importance of riverine networks for regional biodiversity - Rodrigues-Filho, Carlos A. S. (2022)
Fish diversity is generally high in drainage networks in perennial systems. On the other hand, little is known about the importance of drainage networks in semiarid regions. The scant attention given to rivers in semiarid regions so far may in part be explained by the high intermittency and low ramification of these drainage networks and their incorrect classification as systems of low diversity and productivity. In this study, we investigated the importance of the drainage system of an intermittent river system in Brazil with regard to taxonomic and functional bdiversity. To do so, we evaluated the importance of both tributaries (branches) (12 sampling points) and the main stem (7 sampling points).We initially modeled the spatial structure within the branches and the main stem using asymmetric eigenvector maps. We then partitioned b-diversity values between local (biotic and abiotic) and spatial factors (positive spatial autocorrelation). The higher b-diversity values observed for branches were explained mainly by predation and environmental selection. On the other hand, in the main stem, b-diversity was best explained by a combination of environmental conditions and spatial factors. In general, local factors were more important in the functional approach than in the taxonomic approach, supporting their joint use in